Meningkatkan Stabilitas Aspal Porus dengan Penggunaan Filler Limbah Ampas Kopi - Aldo Rizaldi; Sigit Winarto; Ahmad Ridwan; Rendy Kurnia Dewanta (Kadiri University, 2021)
The design mix pavement road needs to be planned appropriately to get the relevant results in its implementation. The selection of materials that easily absorb water becomes one option to parse the occurrence of puddles. Ampas coffee becomes one of the ingredients that can be weighed considering its easy-to-absorb water properties. This study aims to determine the effect of coffee grounds as a mixture of asphalt porous to the characteristics of asphalt porous. The method used is the method of experimental with the manufacture of samples in the laboratory. Variation of asphalt content by 5%, 5.5%, 6%, 6.5%, and 7%. The weight of coffee grounds as filler by 6%. The sample is cylindrical, 4 inches (10.16 cm) in diameter, and 3 inches (7.5 cm) tall. The results of the study obtained optimum asphalt content obtained at a percentage of 7%. With VMA value (Void InMineral Aggregate) 16.13%, VIM (void InMix) 4.58%, VFB (Void Filled Bitumen) 71.62%, Stability 1011kg, Flow Value 3.65 mm, Marshall quotient (MQ) 277kg/mm. Thus, it can be concluded that the results of the study meet the specifications determined by BINA MARGA, with asphalt results more stable, more durable, stronger.